Comparative Viral Sampling in the Sinonasal Passages; Different Viruses at Different Sites - Goggin, Rachel K.; Bennett, Catherine A.; Bassiouni, Ahmed; Bialasiewicz, Seweryn; Vreugde, Sarah; Wormald, Peter-John; Psaltis, Alkis J. (Frontiers in Cellular and Infection Microbiology, 2018)
Background With the emergence of the microbiome as an important factor in health and disease in the respiratory tract standardised, validated techniques are required for its accurate characterisation. No standardised technique has been reported specifically for viral sampling in the sinonasal passages. Aim To optimise viral sampling techniques from the sinonasal cavity. Methods Sterile cytology brushes were used under endoscopic guidance to sample the sinonasal mucosa at time of endoscopic sinus surgery at both the middle and inferior meatuses (MM and IM). DNA and RNA were extracted from the samples and underwent PCR or RT-PCR testing respectively for a panel of fifteen common upper respiratory tract viruses. Results 24 adult patients were recruited for this study. 18/24 (75%) patients were positive for virus in at least one site, while 8/24 (33%) were positive for virus at both sites. The mean number of viruses identified at the two sites were similar (0.875 +/- 0.899 at the MM versus 0.750 +/- 1.032 at the IM). 6/24 (25%) of patients showed no virus at either site, while 3/24 (12.5%) demonstrated the same viral species at both sites. Conclusion Although the number of viruses present at different sites with the nasal cavity are similar, discord exists in the viral species between sites. It is therefore recommended that both sites are sampled in the clinical and research setting better to characterise the viral species within the nasal cavity.